Techno-socio-economic analysis of geological carbon sequestration opportunities. Issue 2 (25th March 2022) - Suleman Kali, Rania Faruq; Fan, Dian; Hazel, Nick; Striolo, Alberto
Abstract : Although geological carbon sequestration is considered one of the pillars required to achieve the goals of the Paris Agreement, only a few demonstration sites are currently being developed around the globe. A workflow is presented here to identify potential new pilot sites. Abstract : Although geological carbon sequestration is considered one of the pillars required to achieve the goals of the Paris Agreement, only a few demonstration sites are currently being developed around the globe. Lab-scale tests, pilot-scale tests, and a few pioneering demonstration projects suggest that substantial amounts of CO2 could be stored in depleted hydrocarbon reserves, saline aquifers, basalts and un-minable coal reserves, albeit a number of risks need to be managed. In this paper, we identify key features of potential geological sequestration sites and study their feasibility via a social-economic assessment, including technical parameters such as volumetric capacity, and reservoir characteristics such as porosity, depth, formation thickness, and initial water saturation. Several geographical sites were further studied in terms of the lifetime duration of a possible geological repository for a preliminary economic assessment. Among the five sites considered, i.e., Cantarell in Mexico, Oloibiri in Nigeria, Frigg in Norway, Rio Vista in the United States of America and Romashkino in Russia, our analysis identifies the Frigg Field as the most favourable site for geological carbon sequestration because of its significant volumetric capacity, no obvious cautionary technical issues, optimistic economic outlook, and extensive social support. Although preliminary, our results suggest that a viable industrial operation could be maintained for several decades in this location, paving the way for the global implementation of geological carbon sequestration required to achieve the goals of the Paris Agreement.